Influência dos métodos de penetração no rosqueamento do aço inoxidável AISI 304L - Costa, Carlos Eduardo (2022)
Among the machining processes, threading is one of the most challenging due to the difficulties in formation and flow of the chips in the cutting zone. The challenge is even greater when machining stainless steel due to the characteristics of this material. The present work analyzes the influence of infeed methods on external turning threading of 304L stainless steel in dry conditions. M class carbide inserts with PVD coating (TiC, Al2O3 TiN) GC 1020 were used in the experiments. Initially, radial, flank and incremental infeed methods with constant depth of cut were compared considering their effects on forces, temperature, chip formation, tool life and thread quality. Subsequently, the modified flank method was evaluated, as well as the use of a constant machining section in terms of tool life. The results showed that the chip obtained by the radial method was the one with the highest values of chip compression ratio. A common feature of all methods was the serrated profile along the edges, characteristic of segmented chips. The radial method showed the highest forces and temperatures, followed by the flank method, while the incremental method resulted in lower values. For all methods employed, both forces and temperatures increased with the number of machined parts due to tool wear. The critical conditions that occur during the stainless steel threading process have caused severe tool tip wear, flank wear and notch wear. The progressive change in the tool geometry generated by wear and adhesions negatively affected the profile of the threads. Compared to radial infeed, the tool life was 28.57% and 71.43% longer for flank and incremental infeed, respectively. The use of the modified flank method provided a longer tool life compared to the others, representing an increase of 44.44% compared to the traditional flank method. Furthermore, when the constant cutting section was used, the wear on the tool tip was reduced, allowing an increase of 23.08% compared to the condition where the depth of cut was kept constant.